2021
DOI: 10.1007/s11908-021-00758-x
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Inequities in Healthcare-associated Infections Under the Shadow of Structural Racism: Narrative Review and Call to Action

Abstract: Purpose of ReviewThe purpose of this study is to review racial and ethnic inequities in the incidence and prevention of healthcare-associated infections (HAIs) in the USA, identify gaps in the literature, and recommend future directions to mitigate these inequities. Recent Findings While some existing literature has identified the presence of racial/ethnic inequities in HAI incidence and outcomes, few studies to date have evaluated whether HAI prevention efforts have mitigated these inequities. Factors contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Our study identified demographic factors, chronic conditions, and acute presentations that providers could be cognizant of while gauging risk of ICU-onset BSI. Black and Hispanic patients displayed a higher risk for ICU-onset BSI compared with White patients further widening existing healthcare disparities even around healthcare-associated conditions (32, 33). Chronic conditions including neurologic and hepatic disorders, coagulopathy, arrhythmias, weight loss, and acute presentations such as trauma, acute respiratory, and gastrointestinal dysfunction were associated with acquisition of ICU-onset BSI.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified demographic factors, chronic conditions, and acute presentations that providers could be cognizant of while gauging risk of ICU-onset BSI. Black and Hispanic patients displayed a higher risk for ICU-onset BSI compared with White patients further widening existing healthcare disparities even around healthcare-associated conditions (32, 33). Chronic conditions including neurologic and hepatic disorders, coagulopathy, arrhythmias, weight loss, and acute presentations such as trauma, acute respiratory, and gastrointestinal dysfunction were associated with acquisition of ICU-onset BSI.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons behind these findings are still uncertain and require further studies to elucidate. However, they may suggest socioeconomic and structural inequities disparately affecting minoritized communities including an inequitable distribution of quality healthcare, differential access to public and private insurance, and insufficient research evaluating and addressing these inequities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of conscious and unconscious biases in medicine have rightly become an important area of research, education, and advocacy. It has been well-documented that clinicians can be biased by patients’ gender, sexual orientation, weight, race, ethnicity, etc, which can ultimately affect diagnoses and subsequent treatment decisions . With the number of applications of artificial intelligence (AI) algorithms in clinical medicine increasing, so has the attention paid to their potential biases .…”
Section: Introductionmentioning
confidence: 99%